1994
DOI: 10.1021/bi00178a023
|View full text |Cite
|
Sign up to set email alerts
|

Water Ring Structure at DNA Interfaces: Hydration and Dynamics of DNA-Anthracycline Complexes

Abstract: In crystallographic structures of biological macromolecules, one can observe many hydration rings that originate at one water molecule, pass via hydrogen bonds through several others, and return to the original water molecule. Five-membered water rings have been thought to occur with greater frequency than other ring sizes. We describe a quantitative assessment of relationships between water ring size and frequency of occurrence in the vicinity of nucleic acid interfaces. This report focuses on low-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 30 publications
2
63
0
1
Order By: Relevance
“…Polygons similar to those described by other authors are found (28 -32). Pentagons predominate, but other polygons are also present, some of them clearly puckered, as found in other cases (32). Such a polygonal structure is reminiscent of that found in some forms of ice, although the most stable form of ice consists of six-membered rings of water molecules (33).…”
Section: Organization Of Counterions: An Ionic Crystal Around the Trimentioning
confidence: 80%
“…Polygons similar to those described by other authors are found (28 -32). Pentagons predominate, but other polygons are also present, some of them clearly puckered, as found in other cases (32). Such a polygonal structure is reminiscent of that found in some forms of ice, although the most stable form of ice consists of six-membered rings of water molecules (33).…”
Section: Organization Of Counterions: An Ionic Crystal Around the Trimentioning
confidence: 80%
“…It has been reported that diVerent antitumor spectra between DR and DX might be caused by the structural diVerences in hydrogen-bonding networks produced from water molecules and either a DR-DNA or DX-DNA complex. DX contains a hydroxyl group at C-14 which forms the hydrogen-bonding to DNA phosphate, producing a conformational structure diVerent from that of DR and DNA (Neidle 1977;Quigley et al 1980;Pohle and Flemming 1986;Frederick et al 1990;Lipscomb et al 1994). The C-14 hydroxyl group may also be related to the ability of the drugs to accumulate especially in cell nuclei in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The latter two were a gift from the laboratory of Loren Williams at the Georgia Institute of Technology. The crystal structures for all three sequences are available from the literature: DNA 10 (15), DNA 6 (16), DNA 6 ·2D (17-19) and DNA 6 ·2A (18,19). All of the samples were warmed to room temperature after the 4 K irradiation and subsequently stored at ~−°C.…”
Section: Methodsmentioning
confidence: 99%